EXPLORING THE THERAPEUTIC BENEFITS OF PARTHENIUM HYSTEROPHORUS: ANTIOXIDANT AND ANTICANCER PERSPECTIVES - Gauri Mukesh Nagarkar,; Pallavi Bajirao Salunkhe,; Avinash Ashok Survase,; Geetanjali Vikas Utekar, (The Bioscan, 2025)
Parthenium hysterophorus is a highly invasive annual herb with significant medicinal properties. Traditionally, it has been used to treat various infectious and degenerative diseases. All parts of the plant act as a bitter tonic, febrifuge, emmenagogue, and antidysenteric. It has strong antibacterial, antifungal, antiviral, anti-parasitic, and anthelmintic effects due to its rich bioactive compounds, including flavonoids, polyphenols, alkaloids, terpenes, and pseudoguaianolides. Flavonoids, in particular, provide antioxidative, hepatoprotective, cardioprotective, anti-inflammatory, antiviral, and anticancer benefits. Despite its medicinal value, Parthenium hysterophorus is one of the world’s most invasive weeds, rapidly colonizing agricultural lands, forests, and disturbed habitats. It produces thousands of seeds each season, spreading aggressively in abandoned areas, roadsides, and irrigation canals, disrupting ecosystems. Recent research highlights its potential in cancer treatment. Zinc oxide nanoparticles (ZnO NPs) derived from the plant show strong antimicrobial and anticancer effects. These nanoparticles selectively kill cancer cells by inducing oxidative stress, mitochondrial damage, and apoptosis while sparing healthy cells. Enhanced ZnO-Ag nanoparticles are even more effective at lower doses, offering promise for cancer therapies, especially where conventional treatments fail. The plant’s flower extract, rich in flavonoids and pseudoguaianolides, may help inhibit tumor Growth and trigger cancer cell death. Exploring its medicinal properties could lead to new plant-based cancer treatments. Additionally, developing sustainable, affordable methods to produce safe nanoparticles for medical use may provide a solution for utilizing this invasive species in a beneficial way.